2022
DOI: 10.1007/s11914-022-00729-8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes and the IL-1 Family in Bone Homeostasis and Disease

Abstract: Purpose of Review Inflammasomes are multimeric protein structures with crucial roles in host responses against infections and injuries. The importance of inflammasome activation goes beyond host defense as a dysregulated inflammasome and subsequent secretion of IL-1 family members is believed to be involved in the pathogenesis of various diseases, some of which also produce skeletal manifestations. The purpose of this review is to summarize recent developments in the understanding of inflammasome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 147 publications
0
4
0
Order By: Relevance
“…Several cytokines including IL-1β and TNF-α were reported to be increased in the PF of women with endometriosis [ 38 ]. In addition, the significance of inflammasome and successive excretion of IL-1 family members is supposed to be intricated in the pathogenesis of various diseases [ 39 ]. In that regard, increased levels of IL-1β and TNF-α were found in animals subjected to endometriosis and treated with the vehicle compared to the sham ( Figure 6 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Several cytokines including IL-1β and TNF-α were reported to be increased in the PF of women with endometriosis [ 38 ]. In addition, the significance of inflammasome and successive excretion of IL-1 family members is supposed to be intricated in the pathogenesis of various diseases [ 39 ]. In that regard, increased levels of IL-1β and TNF-α were found in animals subjected to endometriosis and treated with the vehicle compared to the sham ( Figure 6 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Among the pro‐inflammatory cytokines, IL‐1β strongly induces bone destruction by promoting OC differentiation and activity. IL‐1β is one of the primary members of the IL‐1 family and plays an important role in bone loss following inflammatory infection 51 . In general, LPS stimulates the secretion of various cytokines in the microenvironment, including IL‐1β and TNF‐α, which are involved in LPS‐mediated bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β is one of the primary members of the IL‐1 family and plays an important role in bone loss following inflammatory infection. 51 In general, LPS stimulates the secretion of various cytokines in the microenvironment, including IL‐1β and TNF‐α, which are involved in LPS‐mediated bone resorption. However, compared with the LPS group, these events were inhibited by SIM, which indicated that SIM inhibited autophagy‐related proteins and NLRP3‐related proteins expression did not increase in a time‐dependent manner but did fluctuate, thereby decreasing the high levels of autophagy could be a potential strategy for treating and/or preventing inflammation‐related diseases, 52 including inflammatory bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, senescent cell derived TGFb regulate the ubiquitination of PDGFRb in CaMPCs and contribute to the impaired fracture repair in aged mice. However, we will not exclude the possibility of SASPs, other than TGFb contribute to the protein ubiquitination, because other increased inflammatory cytokines in callus of aged mice, such as TNFa or IL-1 can activate NF-kB signaling 26,27 , which in turn promote the expression of numerous E3 ligases 14,24,25 . Similarly, UPS has multiple targets in MPCs, because we also found other interesting proteins highly ubiquinated, such as Interferon-induced transmembrane protein (another manuscript to Biorxiv).…”
Section: Discussionmentioning
confidence: 99%